Healthy nutrition attitudes of sports science students - Malkoc, Nedim; Yasar, Onur Mutlu; Turgut, Murat; Kerem, Mustafa; Köse, Bereket; Atlı, Ahmet; Sunay, Hakan (Progress in Nutrition, 2020)
The concept of healthy nutrition can be expressed as a naturally occurring concept with human history. It is seen that there is awareness about healthy nutrition activities especially in recent years and it has been increasing both academically and socially. Healthy and adequate nutrition habits are important for both individual and public health. The aim of the study is to examine the attitudes of the senior students, who are educating in the field of sports sciences, towards healthy nutrition. The population of the study consists of students studying at Kastamonu University. The sample of the study consisted of 216 university students from Kastamonu University, School of Physical Education and Sports. Attitude Scale for Healthy Nutrition consisting of 21 items and 4 sub-dimensions adapted by Turkish by Demir and Cicioglu (2019) were used. In order to determine which analysis to use parametric and non-parametric in order to determine the differences between the groups, firstly, whether the data were normally distributed or not was examined within the scope of kurtosis and skewness values. Cronbach Alpha Value of the Attitude Scale for Healthy Nutrition was found to be 90. In conclusion, as a result of the evaluations in the research, the relationship between the participants' gender, age parameters and healthy nutrition attitudes was determined. As a result of the analyzes, the sub-dimension of the highest average score of the participants is the "Information About Nutrition" (X=3.76) sub-dimension. The lowest average score was found in the “Bad Nutrition Habits” (X=2.24) sub-dimension.